{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Stitz-Zeager_College_Algebra_e-book

# The intercept in slope intercept comes from the fact

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: (x) = 3x2 on the other. 1.8 Transformations 1.8.2 107 Answers 1. (a) y = f (x) − 1 (d) y = f (2x) y y 4 (0, 4) 4 3 (0, 3) 3 2 2 1 (1, 0) 1 −4 −3 −2 −1 12 −1 (−2, −1) (2, −1) −2 3 4 x −4 −3 −2 (−1, 0) 2 −2 3 4 x (2, −2) −3 −3 (4, −3) −4 −4 (e) y = −f (x) y (b) y = f (x + 1) y (−1, 4) 4 4 3 3 2 2 (−2, 0) (4, 2) 1 (2, 0) 1 −4 −3 −2 −1 −1 (−3, 0) −2 12 (1, 0) 3 4 x −4 −3 −2 −1 −1 1 2 3 4 3 (2, 0) 4 x −2 −3 (3, −2) −3 (0, −4) −4 −4 (f) y = f (−x) (c) y = 1 f (x) 2 y y 4 4 3 3 2 (0, 4) 2 (0, 2) 1 1 −4 −3 −4 −3 −1 (−2, 0) −1 −2 −3 −4 1 3 4 x (2, 0) (4, −1) (−4, −2) −1 (−2, 0) −1 −2 −3 −4 1 x 108 Relations and Functions (i) y = 1 f (x + 1) − 1 2 (g) y = f (x + 1) − 1 y y 4 4 3 (−1, 3) 3 2 2 1 (−1, 1) −4 −3 −2 −1 −1 1 234 (1, −1) x −2 (−3, −1) −3 1 −4 −3 −2 −1 −1 (−3, −1) −2 1 234 (1, −1) (3, −2) −3 (3, −3) −4 −4 (h) y = 1 − f (x)...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online